Betulinic Acid-Azaprostanoid Hybrids: Synthesis and Pharmacological Evaluation as Anti-inflammatory Agents - Khlebnicova, Tatyana S.; Piven, Yuri A.; Lakhvich, Fedor A.; Sorokina, Iryna V.; Frolova, Tatiana S.; Baev, Dmitry S.; Tolstikova, Tatyana G. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2020)
Background: Prevention and treatment of chronic inflammatory diseases require effective and low-toxic medicines. Molecular hybridization is an effective strategy to enhance the biological activity of new compounds. Triterpenoid scaffolds are in the focus of attention owing to their anti-inflammatory, antiviral, antiproliferative, and immunomodulatory activities. Heteroprostanoids have different pleiotropic effects in acute and chronic inflammatory processes. Objective: The study aimed to develop structurally new and low toxic anti-inflammatory agents via hybridization of betulinic acid with azaprostanoic acids. Methods: A series of betulinic acid-azaprostanoid hybrids was synthesized. The synthetic pathway included the transformation of betulin via Jones' oxidation into betulonic acid, reductive amination of the latter and coupling obtained by 3β-amino-3-deoxybetulinic acid with the 7- or 13-azaprostanoic acids and their homo analogues. The hybrids 1-9 were investigated in vivo on histamine-, formalin- and concanavalin A-induced mouse paw edema models and two models of pain - the acetic acid-induced abdominal writhing and the hotplate test. The hybrids were in vitro evaluated for cytotoxic activity on cancer (MCF7, U- 87 MG) and non-cancer humane cell lines. Results: In the immunogenic inflammation model, the substances showed a pronounced anti-inflammatory effect, which was comparable to that of indomethacin. In the models of the exudative inflammation, none of the compounds displayed a statistically significant effect. The hybrids produced weak or moderate analgesic effects. All the agents revealed low cytotoxicity on human immortalized fibroblasts and cancer cell lines compared with 3β- amino-3-deoxybetulinic acid and doxorubicin. Conclusion: The results indicate that the principal anti-inflammatory effect of hybrids is substantially provided with the triterpenoid scaffold and in some cases with the azaprostanoid scaffold, but the latter makes a significant contribution to reducing the toxicity of hybrids. Hybrid 1 is of interest as a potent low toxic agent against immune-mediated inflammation.
Keywords: cytotoxicity